Coping with people's inflation perceptions during a currency changeover - Eife, Thomas A.; Coombs, W. Timothy (Discussion paper series, 2007)
The discrepancy between popular impressions of how the 2002 changeover to the euro affected prices and its actual impact is perhaps the most surprising consequence of the single currency’s introduction. Following the changeover, perceived inflation rose significantly and returned to its prechangeover level only several months later. This paper argues that people’s inflation misperceptions could have been avoided. Using principles of crisis communication, we identify the mistakes made and present policy recommendations for future changeovers.
Keywords: Arbeitspapier; Graue Literatur